O efeito das orelhas externa e média nas emissões otoacústicas - Do Couto, Christiane Marques; Carvallo, Renata Mota Mamede [UNESP] (Elsevier, 2009)
Characteristics of how external and middle ear resonance frequency can impact the capture of otoacoustic emissions. Aim: to study the impact of external and middle ear resonance frequency in otoacoustic emissions. Study Design: Prospective, clinical, series study. Materials and Methods: Microphone-probe measurements were made in the external ear, together with multifrequency timpanometry distortion product transient otoacoustic emissions in 19 right and 20 left ears from male individuals and 23 right and 23 left ears from female individuals with 17 to 30 years of age. The 85 ears were audiologically normal. Results: We did not observe statistically significant associations between the best otoacoustic emission best frequencies and the occluded external and middle ear resonance frequencies. Conclusion: Response levels for both transient and distortion product otoacoustic emissions are not influenced by the external and middle ear resonances alone. © Revista Brasileira de Otorrinolaringologia.
The effect external and middle ears have in otoacoustic emissions
Keywords: External ear; Middle ear; Spontaneous otoacoustic emissions